Trends in the application of metal Nanobiomaterials in cancer therapy clinical trials - Yun, Zhengcheng; Wei, Junfan (Frontiers in Nanotechnology, 2024)
Background: Cancer is recognized as a major public health problem worldwide, which brings a large number of deaths and serious economic burden. Traditional cancer treatments generally have problems such as limited application, large side effects, and drug resistance. With the rise of nanomedicine technology, its unique advantages in precision drug delivery, imaging sensitivity, assisted drug release, and enhanced drug properties have brought new hope to cancer patients. These therapies, including photothermal therapy, drug delivery, and immunotherapy, use various nanoparticles such as gold and iron-oxide to improve targeted treatment and reduce side effects. The increasing interest in sustainable NP production and safety concerns has driven new research into biocompatible and eco-friendly methods. This study aims to analyze the current research status and global trends in cancer therapy using nanoparticles through a bibliometric analysis.: The Web of Science Core Collection database was searched for publications related to NPbased cancer therapies from January 1995 to December 2023. A bibliometric analysis was conducted using using Bibliometrix Online Analysis Platform, HistCite Pro 2.1, VOSviewer version 1.6.20 and RStudio version 4.3.1, covering metrics like the number of publications, citations, countries, institutions, journals, authors, references, and keywords. Results: A total of 452 articles published in 233 journals. The number of publications on clinical cancer therapy with metal Nanomaterials has shown consistent annual growth. China and Chinese Academy of Sciences were the leading country and institution contributing to this field, respectively.The most prolific author was Zangeneh Mohammad Mahdi, and Biomaterials was the most prolific journal. Key research hotspots identified include keywords such as "gold nanoparticles", "delivery", "drug delivery," "green synthesis," and "cytotoxicity."Conclusion: This is one of the first studies to perform a bibliometric analysis and visualization of publications onclinical cancer therapy with metal Nanomaterials, offering valuable insights for researchers. Future studies should focus on enhancing the efficacy, biocompatibility, and sustainable synthesis of nanoparticles, with an emphasis on their use in personalized medicine and photodynamic therapy.